Penerapan Tujuh Langkah Menyusun Rencana Disiplin Kelas Proaktif Karya Colvin dalam Pembudayaan Hidup Aktif dan Sehat di Sekolah - Widodo -- (Jurnal Pendidikan dan Kebudayaan, 2013)
This study aimed to create new forms of activities as a supplement to create the school conditions that conducive to the cultivation of Active and Healthy Live andÂ  to know the result of the application of forms activities. Research conducted by up to four cycles of action research for four months in one of high schools, secondary schools, and elementary schools.The results shown that: 1) the forms of designed activities can be used as a supplement in the acculturation of an active and healthy life at school, 2) prohibition of misconduct that were previously already left is necessary to be applied by loose tolerances then progressively tightened; 3) teaching learning through competition is an effective way to instill positive behavior; 4) providing tiered reward can be maintained as a positive behavior; 5) providing tiered guidance to improve problem behavior; 6) the data entry is done every day and it is published every four months; 7) the existence ofÂ  other institutions is necessary to sustain the long-term program; 8) the results of the application have shown: (a) increasing penchant to move for students and teachers, sports extracurricular activities, studentsâ€™ awareness of self-health, collective health, and the environment, (b) the school environment changed in a positive direction, and (c) cases of student absence due to illness is also reduced and increasing the number of students who are categorized fitness â€œGoodâ€.ABSTRAKÂ Tujuan penelitian adalah untuk menciptakan bentuk-bentuk kegiatan sebagai suplemen untuk mewujudkan kondisi sekolah yang kondusif bagi pembudayaan hidup aktif dan sehat dan mengetahui hasil dari penerapan bentuk-bentuk kegiatannya. Penelitian dilakukan melalui penelitian tindakan sekolah hingga empat siklus selama empat bulan di salah satu sekolah menengah atas, sekolah menengah pertama, dan sekolah dasar. Hasil penelitian menunjukkan bahwa: 1) bentuk-bentuk kegiatan yang diciptakan dapat dijadikan suplemen dalam pembudayaan hidup aktif dan sehat di sekolah; 2) larangan berperilaku salah yang terlanjur dibiarkan sebelumnya perlu diterapkan dengan toleransi yang longgar kemudian semakin diperketat; 3) pembelajaran melalui kompetisi merupakan cara efektif untuk menanamkan perilaku positif; 4) penghargaan secara berjenjang dapat mempertahankan perilaku positif; 5) pembinaan secara berjenjang dapat memperbaiki perilaku bermasalah; 6) pemasukan data dilakukan setiap hari dan publikasinya setiap empat bulan; 7) peran instansi lain diperlukan untuk mempertahankan program jangka panjang; 8) hasil penerapan telah menunjukkan: (a) peningkatan kegemaran bergerak bagi siswa dan guru, kegiatan ekstrakurikuler olahraga, kepedulian siswa terhadap kesehatan diri, kesehatan bersama, dan lingkungan; (b) perubahan lingkungan sekolah ke arah positif; dan (c) penurunan kasus siswa tidak hadir karena sakit dan peningkatan kebugaran.